Tumor Response Dynamics During First-Line Pembrolizumab Therapy in Patients With Advanced Non–Small-Cell Lung Cancer. (2021) - Nishino, Mizuki; Hong, Fangxin; Ricciuti, Biagio; Hatabu, Hiroto; Awad, Mark M.
Abstract : PURPOSE: The objectives of the study were to characterize the tumor burden dynamics on serial computed tomography scans in patients with advanced non–small-cell lung cancer treated with first-line pembrolizumab and to identify imaging markers for prolonged overall survival (OS). MATERIALS AND METHODS: Eighty-eight patients treated with first-line pembrolizumab monotherapy were evaluated on serial computed tomography scans to characterize their quantitative tumor burden during therapy. Tumor burden dynamics were studied for the association with OS. RESULTS: The overall response rate was 42% (37/88), with the median tumor burden changes at the best overall response of −18.3% (range, −100.0% to +103.6%). Response rates were higher in men than in women ( P = .05) and in patients with higher programmed cell death ligand-1 expression levels ( P = .02). Tumor burden stayed below the baseline burden throughout therapy in 55 patients (63%). In an 8-week landmark analysis, patients with tumor burden below the baseline burden during the first 8 weeks of therapy had longer OS compared with patients who had ≥ 0% increase (median OS, 30.7 v 16.2 months; hazard ratio [HR] = 0.44; P = .01). In the extended Cox models, patients whose tumor burden stayed below the baseline burden throughout therapy had significantly reduced hazards of death (HR = 0.41, P = .003, univariate; HR = 0.35, P = .02, multivariate). Only one patient (1.1%) experienced pseudoprogression with initial tumor increase and subsequent tumor regression. CONCLUSION: In patients with advanced non–small-cell lung cancer treated with first-line single-agent pembrolizumab, tumor burden reduction below the baseline burden during therapy was an independent marker for prolonged OS, which may serve as a practical guide for treatment decisions.